1998
DOI: 10.1074/jbc.273.7.4258
|View full text |Cite
|
Sign up to set email alerts
|

A Major Portion of Synaptic Basal Lamina Acetylcholinesterase Is Detached by High Salt- and Heparin-containing Buffers from Rat Diaphragm Muscle and Torpedo Electric Organ

Abstract: Collagen-tailed asymmetric acetylcholinesterase (AChE) forms are believed to be anchored to the synaptic basal lamina via electrostatic interactions involving proteoglycans. However, it was recently found that in avian and rat muscles, high ionic strength or polyanionic buffers could not detach AChE from cell-surface clusters and that these buffers solubilized intracellular non-junctional asymmetric AChE rather than synaptic forms of the enzyme. In the present study, asymmetric AChE forms were specifically sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…It has been demonstrated that part of the ColQ-AChE complex is covalently associated in the basal lamina, and it thus seems likely that this enzyme represents a very stable pool of AChE, whereas the nonlinked complex may be more dynamic. To date, the proportion of this covalently linked ColQ-AChE is debated, so it may represent the majority of the enzyme (33) or only a minor proportion (34). From our quantification, we estimate that approximately one-third of the AChEs could be very stable, since the labeling could be found weeks after initial saturation.…”
Section: Discussionmentioning
confidence: 75%
“…It has been demonstrated that part of the ColQ-AChE complex is covalently associated in the basal lamina, and it thus seems likely that this enzyme represents a very stable pool of AChE, whereas the nonlinked complex may be more dynamic. To date, the proportion of this covalently linked ColQ-AChE is debated, so it may represent the majority of the enzyme (33) or only a minor proportion (34). From our quantification, we estimate that approximately one-third of the AChEs could be very stable, since the labeling could be found weeks after initial saturation.…”
Section: Discussionmentioning
confidence: 75%
“…These workers provided evidence, in vertebrate skeletal muscle and Torpedo electric organ, that only A forms of AChE interact with heparin and\or other proteoglycans, via motifs on their collagen tails [15,21]. We showed previously that approx.…”
Section: Discussionmentioning
confidence: 97%
“…The A forms are believed to be attached to the basal lamina within the synaptic cleft by interaction with heparan sulphate [15]. The reason for this elaborate polymorphism is, as yet, unknown, but has been ascribed to the functional requirements of different types of synapses [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism for anchoring ColQ involves electrostatic interactions between clustered positive charges of the two sets of heparan sulfate proteoglycan binding sites in the collagen domain with negatively charged basal lamina molecules, such as perlecan. 15,16 However, complete extraction of asymmetric AChE from the basal lamina requires collagenase digestion, 25,26 and this implies an additional nonelectrostatic anchoring mechanism. Consistent with this, Casanueva and collaborators 27 recently found two collagenous molecules (140 and 195-215 kd) in basal lamina that bind asymmetric AChE.…”
Section: Truncation Mutants In Collagen Domain Pre-mentioning
confidence: 99%